2010
DOI: 10.1073/pnas.1001925107
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious inhibition separates two forms of cognitive control

Abstract: In the human brain, cognitive-control processes are generally considered distinct from the unconscious mechanisms elicited by subliminal priming. Here, we show that cognitive control engaged in situations of response conflict interacts with the negative (inhibitory) phase of subliminal priming. Thus, cognitive control may surprisingly share common processes with nonconscious brain mechanisms. In contrast, our findings reveal that subliminal inhibition does not, however, interact with control adaptation-the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 41 publications
(66 reference statements)
12
88
2
1
Order By: Relevance
“…In contrast, in the current study congruency effects must reflect control exerted in response to the imitative conflict rather than in preparation for conflict, since the need for control was unpredictable. Differences between preparatory and reactive control mechanisms have been observed in other domains (Braver et al 2007; Boy et al 2010; Braver, 2012) and are plausible in this context as well. For example, in a situation where imitation control can be implemented in advance (e.g.…”
Section: Discussionsupporting
confidence: 59%
“…In contrast, in the current study congruency effects must reflect control exerted in response to the imitative conflict rather than in preparation for conflict, since the need for control was unpredictable. Differences between preparatory and reactive control mechanisms have been observed in other domains (Braver et al 2007; Boy et al 2010; Braver, 2012) and are plausible in this context as well. For example, in a situation where imitation control can be implemented in advance (e.g.…”
Section: Discussionsupporting
confidence: 59%
“…Some recent work has produced support for the basic existence of rapid within-trial processing adjustments (Taylor et al, 2007; Appelbaum et al, in press), and has suggested that these may be mediated by principally distinct mechanisms than those that underpin across-trial adjustments (Boy et al, 2010). However, whether CSEs are an expression of the former or the latter currently remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…It is influenced by task difficulty within a block and percentages of expected conflict, so that with a high rate of conflicted trials the overall conflict effect is reduced (Tzelgov et al, 1992), presumably due to strategic intended inhibition of the irrelevant route. There is some evidence that these mechanisms are differential and represent two separate mechanisms (Boy, Husain, & Sumner, 2010;Hommel, Proctor, & Vu, 2004;Iani, Rubichi, Gherri, & Nicoletti, 2009;Osman et al, 2000) but this is still under debate as some suggest that they reflect one process (Soetens, Maetens, & Zeischka, 2010).…”
Section: Simon Taskmentioning
confidence: 94%